Kembar Mayang Tradition in Javanese Wedding Ceremony in Dusun VI, Nagur Village, Tanjung Beringin District, Serdang Bedagai Regency - Ayu Lestary; Jufri Naldo; Nabila Yasmin (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This research employs qualitative methods with an anthropological approach to understand the significance of the Kembar Mayang tradition in Javanese weddings. The anthropological approach investigates human societies and behaviors, focusing on cultural practices and their meanings. Data collection was conducted through a combination of library research, field observations, and interviews with relevant sources to ensure the validity of the information and comprehensive documentation. The study reveals that Javanese people view marriage as sacred, filled with rituals imbued with prayers for a harmonious domestic life. One prominent tradition in Javanese weddings is Kembar Mayang, symbolizing the union of two hearts into one, reflecting shared goals for a peaceful and blessed household. The Kembar Mayang ritual, made of flowers and leaves, embodies important cultural values and is essential in traditional Javanese wedding ceremonies.